Peralihan Regulasi Dari Undang-Undang Nomor 8 Tahun 1971 KeUndang-Undang Nomor 22 Tahun 2001 Tentang Minyak Dan GasBumi - Iskatrinah; Doni Adi Supriyo (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2022)
The enactment of Law Number 22 of 2001 concerning Oil and Gas, is an important milestone in regulating oil andgas mining business in Indonesia. One of the interesting provisions is regarding the production sharing contract.However, in this study, the formulation of the problem that will be reviewed is the history of the birth of LawNumber 22 of 2001 concerning Oil and Gas. The method used in this discussion is the normative juridical methodthrough literature studies such as literature books and Law Number 8 of 1971; Law Number 22 of 2001concerning Oil, Gas and Natural Gas by doing a comparison or comparison of the two laws and regulations. Thespecifications used in this discussion are Analytical Descriptive, which describes the facts regarding provisionsregarding oil and gas and natural gas. In order to fulfill the wishes of foreign investors, the economic reformagenda contained in the letter of intense, includes the energy sector reform program. The energy sector reform isstated in the agreement item letter F (The energy Sector) in the Memorandum of Economic and Financial Policies(Letter of Intense), January 20, 2000.